Characterization of bacillus isolates of potato rhizosphere from Andean soils of Peru and their potential PGPR characteristics - Calvo, P (2010)
A. Lopez-Lopez, M. A. Rogel-Hernandez, Monica Rosenblueth, and L. Raymundo are thanked for technical assistance. This research was supported by Consejo Nacional de Ciencia y Tecnologia (Concytec), Integrated Crop Management Division of International Potato Center (CIP), FDA biol-111/UNALM, DGAPA-PAPIIT IN200709 project, and Red Biofag-Cyted. We are grateful to Dr. Andreas Oswald (CIP) for his support in the collection of samples.